EVALUASI PENERAPAN SISTEM AKUNTANSI PENGELUARAN KAS PENGGAJIAAN PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI UTARA - Roring, Pricilla Roxenne; Karamoy, Herman; Pangemanan, Sifrid (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The cash expenditure accounting system  is an activity that  the government cannot do without, the government reinforces caution in engaging in activities related to cash receipts and cash disbursements. The problem in this research  is how  the application of  cash accounting system of Civil Employees at the Regional Civil Service Agency of North Sulawesi Province is implemented. The objective of this research is to evaluate the application of Cash Expenditure Accounting System, especially the payroll of civil employees. The  type of  this  research  is descriptive, using  the qualitative method. Where an analysis collects, organizes, and manages, in order to provide a picture of a particular situation  so that it can be deduced. The results of this study indicates that the payroll cash expenditure accounting system of civil employees at the Regional Civil Service Agency of the North Sulawesi Province has been applied well in accordance with the qualitative characteristics of the financial reports as it can be proven with existing data. In conclusion regarding the Cash Expenditure Accounting System at the Regional Civil Service Agency of North Sulawesi Province is in accordance with government regulation No.13 since 2006.Keywords : Accounting system, cash expenditure, evaluation